1981
DOI: 10.1038/289258a0
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and formation of the transforming gene of a mouse sarcoma virus

Abstract: The complete nucleotide sequence of the transforming gene of a mouse sarcoma virus has been determined. It codes for a protein of 374 amino acids. The nucleotide sequence of the junctions between a murine leukaemia virus and cellular sequences leading to the formation of the viral transforming gene have also been elucidated. The viral transforming sequence and its cellular homologue share an uninterrupted stretch of 1,159 nucleotides, with few base substitutions. The predicted amino acid sequence of the mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(115 citation statements)
references
References 39 publications
7
107
1
Order By: Relevance
“…However, together the helper and vector genomes still retain all essential viral functions and could generate competent virus by an illegitimate recombination. Detailed studies of Moloney murine sarcoma virus (47,48) and Moloney mink cell focus-forming virus (2) suggest that recombination can involve both cellular and viral information and that extensive nucleic acid sequence homology is not an absolute prerequisite for formation of recombinant virus. Although nonhomologous recombination is not well understood, it has been shown that unrelated DNAs transfected into L cells recombine close to regions of partial sequence homology (3).…”
Section: Resultsmentioning
confidence: 99%
“…However, together the helper and vector genomes still retain all essential viral functions and could generate competent virus by an illegitimate recombination. Detailed studies of Moloney murine sarcoma virus (47,48) and Moloney mink cell focus-forming virus (2) suggest that recombination can involve both cellular and viral information and that extensive nucleic acid sequence homology is not an absolute prerequisite for formation of recombinant virus. Although nonhomologous recombination is not well understood, it has been shown that unrelated DNAs transfected into L cells recombine close to regions of partial sequence homology (3).…”
Section: Resultsmentioning
confidence: 99%
“…Our data do not indicate whether strict conservation of this residue is required for stability or whether replacement with other hydrophobic residues might preserve protein stability and activity. For (39), Xenopus c-src (54), Drosophila src and ash (20), v-src (11,46,58), v-fqr (36), v-yes (26), v-ros (37), v-fps (52), v-fes (19), v-fms (18), c-fms (9), v-mil (v-mht) (25,56), v-raf(32), IskT (tck) (33,63), human insulin receptor (61), v-mos (62), human epidermal growth factor (EGF) receptor (12,61), c-erbB-2 (67), v-erbB (66), neu (2), and v-abl (44). The chicken c-src, v-src, v-fgr, v-yes, v-ros, v-fps, v-fes, v-abl, human EGF receptor, and v-erbB sequences were aligned as in Hunter and Cooper (21).…”
Section: Discussionmentioning
confidence: 99%
“…Not all viral transforming proteins that display associated kinase activity phosphorylate tyrosine. The guanine nucleotide-binding protein (p21) encoded by Harvey MuSV v-mos gene autophosphorylates at threonine (30), A computerized search for similarities among the predicted amino acid sequences of avian sarcoma virus p6src, the MoMuSV v-mos gene product first observed by Van Beveren et al (2), and the catalytic subunit ofcAMP-dependent protein kinase has revealed potential ATP-binding sites in all three proteins (31). Such a binding'site within the mos gene is consistent with our results which would suggest that the mos portion of P85gag-ms is a protein kinase.…”
Section: Discussionmentioning
confidence: 99%